Avaliação da percepção do impacto da internet na relação médico-paciente entre alunos do 3º ao 6º ano e professores da UNIFENAS - BH - Atem, Cláudio Negrão Tanus (2019)
Introduction: The internet is currently an important source of information about health, nevertheless it carries potential harm, as misinterpreted or confusing information can generate anxiety and stimulate self-medication. The popularization of access to health information, as well as the strengthening of person-centered medicine, has the potential to influence the doctor - patient relationship, as the doctor is no longer the sole holder of knowledge and needs to share “power” with the patient in their guidelines and conduct. Objective: To evaluate the perception of patients’ use of the internet to obtain information about their illness and the association with the Power-sharing attitude in the doctor-patient relationship between medical students and their teachers. Methods: Quantitative, observational, cross-sectional study, which included medical students from 3 ͬ ͩ and 6 ͭ ͪ year of UNIFENAS – BH and their respective teachers of outpatient practice. The outcomes of interest were assessed by means of a questionnaire adapted to assess people`s perception of internet use to obtain information about their illness and the patientpractitioner orientations scale (PPOS) power subscale. Results: 215 students participated in the study, 60% female, with a mean age of 24±3,1 yars, and 30 teachers, 50% female, with a mean age of 42±7,8 years. The mean score of positive perception of the influence of the internet on he physician-patient relationship was the same among students in the 3 ͬ ͩ and 6 ͭ ͪ grades (3,37±0,64 and 3,22±0,57, respectively); p = 0,052 and lower when compared to teachers(3,86±0,64; p<0,001). Regarding the Power-sharing attitude, the score between the 3 ͬ ͩ and 6 ͭ ͪ grade students was also equal (4,17±0,69 vs. 4,51±0,65 respectively, p=0,036). The students, regardless of the current year, have a greater attitude of sharing in the decision process when compared to male students (p<0,009). There was a direct correlation between sharing and internet perception, being weak among 3 ͬ ͩ and 6 ͭ ͪ grade students (r=0,31; p<0,05) and moderate among teachers(r=0,53;p=0,003). Conclusions: Both students and teachers have a positive perception of the impact of internet perception and the Power subscale of PPOS was weak among students and moderate among teachers